High-sensitivity colorimetric sensor based on oxidase-like Mn3O4 nanozyme for Cys detection - Junting Liang; Dihan Duan; Lubing Sun; Jinming Li; Mengke Wang; Ziyi Chang; Rick F. Thorne; Chuanliang Chen; Demin Duan (Sensors and Actuators Reports)
Cysteine (Cys) is essential for numerous physiological processes and play a vital role in disease diagnostics, underscoring the necessity for effective and sensitive detection techniques for Cys. In this research, we introduce an ultrasensitive colorimetric approach based on oxidase-like Mn3O4 nanozymes. The nanozymes were synthesized through a straightforward wet chemical method and displayed a flower-like globular morphology, showing remarkable oxidase-like catalytic performance with a low Km value of 0.1896 mM and a high Vmax of 2.8 × 10⁻⁷ M s⁻¹. By leveraging the outstanding catalytic activities of Mn3O4 nanozymes and optimizing the TMB concentration, we developed a novel and sensitive colorimetric sensor for Cys detection. Experimental results indicated a detection range for Cys between 0.5 and 45 μM, with a lower limit of detection (LOD) of 0.02636 μM. This established method for detecting Cys reveals significant promise for the advancement of effective sensing systems.